Bio-active Spectra of Plumbagin - Poul, B.N.; Mukadam, D.S.; Dama, L.B.; Jadhav, B.V. (Asian Journal of Chemistry, 2010)
The bio-active compound plumbagin is isolated from Chitraka, Plumbago zeylanica Linn. The anti-bacterial and anti-fungal activities of Plumbagin were studied by using the Disc-Assay Method against a series of pathogenic micro-organisms which are responsible for severe neasopharyngeal, respiratory, cardio-vascular, dermal, neuromuscular, gastro-intestinal and genito-urinary tract infections. Plumbagin shows broad spectral antimicrobial activity against selected pathogenic micro-organisms in vitro and in vivo.